Techno-economic Analysis of DC Microgrid and its Distributed Control Strategies with Fault Current Mitigation Technique for Power Sharing and Voltage Regulation - Shahid Ullah, Khan (Springer, 2020)
Recent research on DC systems revealed that DC microgrids can be an efficient, reliable, and economical solution to avoid the inherent issues associated with AC power integration such as frequency control, harmonics, and synchronization. One major concern of the DC microgrids with multiple converters is the control of power-sharing, aiming to maintain the voltage profile, particularly during system disturbances. Under the worst scenarios, DC microgrid operation may be completely impacted if properly distributed control strategies are not considered with an effective protective approach to eliminate the fault currents. The ongoing studies presented in the area of DC microgrid control reflect its importance, however, the stability of an isolated DC microgrid in terms of power sharing and voltage regulation especially under fault conditions is not sufficiently addressed in the literature. In the first objective of this research, a framework has been proposed to assess the technical benefits of implementing either AC or DC distribution considering the existing AC infrastructure. Further, a Hybrid Optimization of Multiple Electric Renewables (HOMER) based analysis has been carried out to determine the most economical and optimal size of an isolated solar PV system with its energy storage to be connected either as an AC or DC microgrid. From the obtained outcomes of the above-mentioned framework, a distributed secondary control strategy has been developed in the second objective. This approach is based on average-voltage/average-current control and circulating current minimization for DC bus voltage regulation and maintaining power-sharing under different scenarios. In that sense, an additional current feedback loop is introduced to modify the microgrid reference voltage during overload conditions to minimize the line voltage drop and distribution losses. Finally, to mitigate the vulnerability of isolated DC microgrid control due to fault conditions, a preventive scheme of controllable fault current limiter (C-FCL) has been designed in the third objective. The C-FCL acts in a coordinated manner with the implemented control of power sharing and voltage regulation. This research study was carried out using the HOMER optimizer and MATLAB/Simulink with small-scale experimental validation. The results show that applying DC voltage magnitude equal to the peak value of AC voltage reduces the power loss of DC microgrid up to half value compared to AC microgrid and the voltage drop in the distribution lines reduces by 29.3%. It is revealed that the proposed control strategy has better voltage regulation, and power-sharing performance without any significant deviation imposed by variation in PV generation as well as load switching. Further, using the proposed C-FCL protective scheme can limit the fault current magnitudes for different fault locations, keeping the converters operating in a safe mode during fault conditions. The C-FCL increases the fault clearance time for the protection system providing more efficient and reliable operation of the DC microgrid.